2021
DOI: 10.1016/j.scitotenv.2021.149014
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pharmaceuticals use during the first wave of COVID-19 pandemic in Athens, Greece as revealed by wastewater-based epidemiology

Abstract: Since 2019, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), impaired public health with considerable morbidity and mortality due to the lack of vaccines and effective treatment. The severe disease mainly harmed adults with predisposing medical comorbidities (such as heart disease, hypertension, chronic lung disease), while it can occur in healthy individuals that may be asymptomatic. Wastewater-based Epidemiology (WBE), a non-invasive, objective, chemical tool was used to monitor and estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…With respect to the aquatic environment, a significant analytical challenge exists for the chemical characterisation, measurement, and environmental risk assessment (ERA) of many compounds with high spatiotemporal coverage. Multiresidue analysis methods currently exist for hundreds to thousands of compounds in water samples [4], but these often rely on analyte concentration steps such as solid phase extraction (SPE) to achieve the required sensitivity. For chemicals of emerging concern (CECs), this can prove challenging in terms of achieving sufficient chemical selectivity to ensure the widest range of compounds present in a sample can be extracted and enriched for instrumental measurement.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the aquatic environment, a significant analytical challenge exists for the chemical characterisation, measurement, and environmental risk assessment (ERA) of many compounds with high spatiotemporal coverage. Multiresidue analysis methods currently exist for hundreds to thousands of compounds in water samples [4], but these often rely on analyte concentration steps such as solid phase extraction (SPE) to achieve the required sensitivity. For chemicals of emerging concern (CECs), this can prove challenging in terms of achieving sufficient chemical selectivity to ensure the widest range of compounds present in a sample can be extracted and enriched for instrumental measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In Togo, 34.2% of survey participants ( n = 955) reported that they self-medicated after experiencing COVID-19-like symptoms with 2.0% using chloroquine and hydroxychloroquine (Sadio et al 2021 ). In Greece, there was a significant decrease in the consumption of antihypertensive, diuretic, and antilipidemic drugs during lockdown (Galani et al 2021 ). Hence, the strict lockdowns enacted by various countries across the globe may have decreased access to medical facilities such as clinics, hospitals, and pharmacies to non-COVID-19 patients, which could result in a decrease in consumption of non-COVID-19 related pharmaceuticals (Galani et al 2021 ; Oikonomou et al 2020 ).…”
Section: Consumption Patterns Of Covid-19 Related Pharmaceuticalsmentioning
confidence: 99%
“…In Greece, there was a significant decrease in the consumption of antihypertensive, diuretic, and antilipidemic drugs during lockdown (Galani et al 2021 ). Hence, the strict lockdowns enacted by various countries across the globe may have decreased access to medical facilities such as clinics, hospitals, and pharmacies to non-COVID-19 patients, which could result in a decrease in consumption of non-COVID-19 related pharmaceuticals (Galani et al 2021 ; Oikonomou et al 2020 ). Additionally, the COVID-19 pandemic has contributed to the disruption of the supply chain of generic drugs sourced from countries with strict lockdown procedures and shift in consumption of branded drugs towards COVID-19 drugs leaving non-COVID-19 patients untreated ( https://cen.acs.org/business/outsourcing/COVID-19-reshaping-pharmaceutical-supply/98/i16 ).…”
Section: Consumption Patterns Of Covid-19 Related Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater samples collected from the wastewater treatment plant (WWTP) of Athens (Greece), before (2019) and during the COVID-19 pandemic (2020), revealed a remarkable increase in antiviral drugs (170%), antibiotics (57%), and hydroxychloroquine (387%), which are most pharmaceutical drugs applied to treat COVID-19, along with paracetamol (198%) ( Galani et al, 2021 ). In addition to the pharmaceuticals potential ecotoxicity ( Galani et al, 2021 ), it can increase microorganism's antidrug resistance (ADR) ( Kumar et al, 2021 ), thus imposing a severe threat to human and animal health.…”
Section: Negative Effects Of Covid-19 Pandemic On the Environment – An Intimidating Journeymentioning
confidence: 99%